Using type and temporal semantic enrichment to boost content discoverability and multilingualism in the Greek cultural aggregator SearchCulture.gr. (2018) - Georgiadis, Haris; Papanoti, Agathi; Paschou, Maria; Roubani, Alexandra; Hardouveli, Despina; Sachini, Evi
Most aggregators face challenges regarding searchability, discoverability and visual presentation of their content due to metadata heterogeneity across the collections. Particularly for cultural and historical material, keyword-based searching is far from sufficient. Structured item types and temporal information are key metadata for the discoverability of cultural heritage content. We developed an innovative metadata enrichment and homogenisation scheme for types and temporal information that is both effective and user-friendly and we embedded it in the ingestion workflow of SearchCulture.gr, the Greek cultural heritage aggregator developed by the National Documentation Centre (EKT). Two key components of the enrichment scheme are Semantics.gr, a platform for publishing vocabularies that contains a mapping tool for massive semantic enrichment, and a parametric tool for chronological normalisation. We enriched and homogenised the aggregated content with respect to types and temporal information which subsequently allowed us to develop advanced multilingual search and browsing features, including hierarchical navigation on types and historical periods, searching and faceting on types, time spans and historical periods, a tag cloud of types and an interactive timeline/histogram.